Different attentional dysfunctions in eEF2K−/−, IL1RAPL1−/− and SHANK3Δ11−/− mice. (27th March 2019) - Ponzoni, Luisa; Sala, Carlo; Verpelli, Chiara; Sala, Mariaelvina; Braida, Daniela
Abstract : A common feature of several psychiatric disorders is the attentional impairment. eEF2K −/−, IL1RAPL1 −/− and SHANK3Δ11 −/− mice were used as animal models consistently linked to changes in synaptic plasticity, learning and memory. All knockout (KO) mice and their corresponding littermates were submitted to the novel object recognition (NOR) and visual object recognition (VOR) tasks. In the NOR, eEF2K −/− mice exhibited a normal performance in terms of mean discrimination index, while SHANK3Δ11 −/− and IL1RAPL1 −/− mice were impaired when a delay of 2 and 24 hours was introduced. Surprisingly, when submitted to VOR, where the two objects were replaced with two shapes delivered from two iPods, all the mutant mice performed worse than those in the NOR. In VOR, the application of motion to different shapes, to increase attention, improved performance in eEF2K −/− and IL1RAPL1 −/− but not in SHANK3Δ11 −/− mice. In SHANK3Δ11 −/− mice, attentional deficit was also present even if different motions were applied to the same shapes or when these mice were repeatedly exposed for 5 days to the context. Behavioral analysis showed that eEF2K −/− and IL1RAPL1 −/− mice had a good flexibility tested in the T‐maze. eEF2K −/− showed normal self‐grooming. On the basis of previous literature data indicating that SHANK3Δ11 −/− showed impaired flexibility and reduced sociability, we identified in this genotype the most exhaustive model showing all the core symptoms of autism spectrum disorder including a heavy visual attention deficit. These findings show the importance of VOR to identify mouse models of autism. Abstract : The application of different motions to shapes in the VOR rescued attentive deficit in eEF2K −/− and IL1RAPL1 −/− but not in SHANK3Δ11 −/− mice.